Pedigree analysis of two brothers with severe oligozoospermia caused by maternal inv(X) (p22.3, q22) chromosome abnormality. (30th April 2020) - Ge, Yunsheng; Sha, Yanwei; Cai, Meijiao; Chen, Xiaolu; Sha, Yankun; Xu, Xiaohui
Abstract: Sex chromosome abnormality (SCA) is one of the major causes of male spermatogenesis dysfunction. In our study, we sought to investigate the novel X chromosome inversion leading to severe oligozoospermia. Here, we report two brothers with severe oligozoospermia without any other abnormal clinical phenotype. The chromosome karyotypes in peripheral blood of both brothers were 46, Y, inv (X) (p22.3, q22), and no Y chromosome microdeletion was found. The karyotype of their mother was 46, X, inv (X) (p22.3, q22) and that of their father was 46, XY. This is the first report in China that X chromosomal inversion, 46, Y, inv (X) (p22.3, q22), is associated with severe oligozoospermia. This inversion may be a direct genetic risk factor for spermatogenesis.